The economics of the natural gas shortage (1960-1980) - MacAvoy, Paul W.; Pindyck, Robert S. (Amsterdam : North-Holland Pub. Co. ; New York : American Elsevier, 1975)
This study reports o the the third phase results of a National Science Foundation project to develop an econometric policy model of natural gas. The plan of the book gives an introduction to the natural gas shortage and the technical-regulatory frames of reference for explaining the present extent of the shortage, followed by an analysis of alternative policies for dealing with the shortage, using the econometric policy model described in technical detail in chapters 3,4, and 5.
Includes index.
Includes bibliographical references: p. 251-256.
ne 11/107/2019
Loans
Keywords: Natural gas